Effects of elderberry (Sambucus ebulus) feeding on broiler performance - Saei, M; Seidavi, A; Bouyeh, M (Journal of the Hellenic Veterinary Medical Society, 2026)
This study aimed to evaluate the effects of elderberry (Sambucus ebulus) feeding on performance, carcass characteristics, biochemical and antioxidant blood parameters, immune system, sensory and taste traits and fatty acid profile of meat in broiler chickens. Biological experiments were planned in a completely randomized design including three treatments of 0, 0.5 and 1% elderberry (Sambucus ebulus) fruit powder with 5 replications and 10 birds per replication. In total, 150 broiler chickens of the Ross 308 strain were fed corn and soybean meal-based diets during three periods: starter (1-11 d), grower (12-21 d) and finisher (22-42 d). The performance results showed that in the finisher period (22 to 42 d) a significant difference was observed for body weight and feed conversion ratio (FCR), so that for body weight in this period, the best performance was related to the 0.5% elderberry treatment (P<0.05). Also, the worst (highest) FCR was observed for the group fed with the 1% elderberry group, which was significantly higher in terms of quantity than the control and 0.5% elderberry groups (P<0.05). The linear equation for FCR (y = 0.062x + 1.7417 with a coefficient of determination equal to 0.52) and the quadratic equation (y = -493.8x2 + 386.1x + 1640.6 with a turning point of 0.39) were obtained for body weight, which was significant (P<0.05). In addition, performance in the entire period (age 1 to 42 d) also showed a significant difference between FCR in the 1% elderberry group (1.616) versus the control treatment (1.583) and the 0.5% elderberry treatment (1.577) (P<0.05), and the linear equation for this trait was also significant (y = 0.033x + 1.5755 with a coefficient of determination of 0.62 and a significance level of 0.037). In addition, the results of blood biochemical parameters for the traits glucose, cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), atherogenic index, uric acid, albumin, total protein, iron, calcium, alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA) and total antioxidant capacity (TAC) showed significant differences (improving trend) among the experimental treatments (P<0.01). Also, in all traits (except blood triglycerides, phosphorus and uric acid) a significant difference was observed between the control group compared to the effects of contrast with elderberry (zero group compared to two levels of 0.5 and 1% elderberry) and also for all mentioned blood traits except blood triglycerides, phosphorus and uric acid, there were significant linear equations between the effects of the treatments. Results related to the immune system also showed that the control treatment had a higher and significant Antibody Titr (35day-SRBC test) value than each of the 0.5 and 1% elderberry treatments, and the contrast effect of the control group was also significantly higher than the groups fed with elderberry (P<0.01). Spleen weight was the lowest in the 1% elderberry treatment (P<0.05). The results of the taste and sensory traits of chicken breast meat were only affected by the 0.5% treatment compared to the control and 1% treatments (P<0.01), and the results of the contrast effects of the control group compared to the elderberry treatments, the quadratic equation (y = -4x2 + 4.4x + 7.4 with a turning point of 0.55) for meat smell was significant (P<0.05). Overall, the results showed that dietary supplementation with elderberry has a positive and promising role on blood biochemical parameters and immunity and in improving the health of chickens as well as maintaining product quality, but in choosing high levels of intake with the source, bird performance must be managed.